MANAGEMENT OF SUSTAINABLE MINING OF COAL RESOURCES IN UKRAINE - Volkov, V.; Horoshkova, L.; Khlobystov, Y. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The dynamics of coal resources mining in Ukraine are analyzed in the article. It is proved that there were indices fluctuations, i.e. volumes of extraction, and growth rates during 10 years. The approximation of growth rates of coal mining resources by polynomial function using the trend line is made. It is determined that studied indices fluctuation have cyclical pattern, correlate to each other and depend on country`s economic and political situation. It is proposed to make forecasts of the extraction volumes based on national cyclical economic development. It is proved that balanced mining should solve the problem of mineral deposits sustainable exploitation. It is proposed to use the patent-protected author’s methodology to forecast the development of complex systems to manage sustainable mining of coal resources in Ukraine. The developed model will allow managing volumes of extraction of technologically related minerals in correlation with the volumes of exploitation.